Signs of sustainability: promoting the environmental and aesthetic impact of green infrastructure on campus - Goold, Alexina (My University, 2025)
Cities have struggled to integrate green infrastructure solutions due to an underwhelming lack of support and acceptance. A typical social barrier that causes this slow integration is the lack of general public education and awareness of green infrastructure systems. This lack of education also affects many other barriers, including funding green infrastructure projects and political barriers. A need has been expressed to encourage educational opportunities that people can easily access and understand. As landscape architects, we should be one of the main contributors to this cause, helping increase public acceptance through educational opportunities. This research aims to aid in collecting and organizing information on local green infrastructure projects to create an educational tour with informative and engaging signage. To collect and organize the information, site inventory and observational photography were used to support a projective design of tour fliers and signage. The result will include projective signage for six sites on the Kansas State University campus and a coordinating tour flier to inform people about the tour and sites.
Keywords: Educational signage; Campus design; Green infrastructure; Tour; Engagment tools for signage